2018
DOI: 10.18805/lr-3906
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genetic variability and character association for yield and yield related traits in french bean (Phaseolus vulgaris L.)

Abstract: Eighteen genotypes of french bean were evaluated for genetic variability and correlation studies for pod yield and its attributing characters. Both GCV and PCV corresponded closely for all the characters indicating low environmental influence. Highest GCV and PCV were recorded for seed weight per pod (145.12 % and 144.87%, respectively). The highest heritability estimate was observed for number of pods per plant (99.71 %). Pod yield per plant was significantly and positively correlated with number of pods per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Path coefficient analysis utilizes the correlation coefficient values and depicts whether the trait influences the yield directly or by indirect means (Lyngdoh et al, 2018). At the genotypic level displayed the highest direct effects of kernel width, followed by number of pods per plant, and pod length with pod yield in a positive manner (Fig 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Path coefficient analysis utilizes the correlation coefficient values and depicts whether the trait influences the yield directly or by indirect means (Lyngdoh et al, 2018). At the genotypic level displayed the highest direct effects of kernel width, followed by number of pods per plant, and pod length with pod yield in a positive manner (Fig 1a).…”
Section: Resultsmentioning
confidence: 99%
“…At genotypic level, seed yield per plant have significant positive correlation with protein was recorded in 29 different genotypes of Pea (Pisum sativum L.) (Toppo et al, 2017). Highest GCV and PCV were recorded for seed weight /pod (145.12% & 144.87%, respectively (Lyngdoh et al, 2017). Significantly positive GCV were recorded in green pod yield with no.…”
Section: Correlationmentioning
confidence: 91%
“…For seed weight /pod, plant height, pods /plant, no. of leaves /plants, pod weight & pod yield/plant, maximum variability was found in eighteen different genotypes (Lyngdoh et al, 2017). In nine French bean (Phaseolus vulgaris L.) genotypes grown at two different locations highest variability for primary branches, grain yield, hundred seed weight & number of pods /plants was recorded (Wondimu et al, 2017).…”
Section: Genetic Variabilitymentioning
confidence: 97%
“…In this regard, Raffi and Nath (2004) found highest GCV for 20-seed weight (42.19%), followed by seed yield per plant (39.35%) while, number of days to 50% flowering and number of days to maturity had the lowest ones. Also, Lyngdoh et al (2018) found high GCV for seed weight per pod (144.87%), plant height (91.35%), and number of leaves per plant (30.92%).…”
Section: Genetic Variabilitymentioning
confidence: 98%
“…The most common clustering methods in plant breeding, are optimization methods such as the Tocher optimization method (Rao, 1952) and hierarchical methods such as unweighted pair group method with arithmetic mean (UPGMA) (Sokal and Michener, 1958). Both of such clustering methods have been used to estimate the genetic diversity in beans (Ceolin et al, 2007, Barelli et al, 2009, Razvi, 2011, Carvalho et al, 2016, de Souza et al, 2017, Lyngdoh et al, 2018, Wani et al, 2018, and Sharma et al, 2019. Moreover, it is necessary for plant breeders, to distinguish the most contributing traits towards the genetic diversity, to consider them as selection criteria and discard those with a little contribution.…”
Section: Introductionmentioning
confidence: 99%